2018
DOI: 10.1111/cid.12699
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk factors for maxillary sinus membrane perforation and treatment outcome analysis

Abstract: Background Most common complication of sinus floor elevation (SFE) is sinus membrane perforation (SMP). Purpose To investigate the correlation between SMP and potential risk factors and to evaluate SMP treatment outcomes. Materials and Methods This study included patients who had undergone a SFE at Division of Oral Surgery and Orthodontics, Medical University of Graz from 2013 to 2017. Analysis of patients' records and CBCT focused on patient‐related risk factors (sinus contours, thickness of membrane and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(97 citation statements)
references
References 38 publications
(81 reference statements)
8
80
2
2
Order By: Relevance
“…Sinus membrane perforations can occur due to thin membranes, 6,20 operator error, 8 maxillary sinus contours, 6 the presence of septum, 21 and a small residual bone height 4 . In this study, 22 patients underwent reentry LSFE.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Sinus membrane perforations can occur due to thin membranes, 6,20 operator error, 8 maxillary sinus contours, 6 the presence of septum, 21 and a small residual bone height 4 . In this study, 22 patients underwent reentry LSFE.…”
Section: Discussionmentioning
confidence: 94%
“…Maxillary sinus mucosa perforations are the most common complication during LSFE, with a reported incidence of 7%‐56% 3 . Despite various updates in both the surgical technique and instruments, problems remain unavoidable 6,17 . Previous studies showed that when the perforation was small, or less than 10 mm, the perforation could be repaired by collagen membrane coverage or by suture delicately 5,7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased sinus mucosal thickness (SMT) could be caused by a variety of inflammatory symptoms, and the influencing factors include patient-related factors like age or smoking history; tooth-related factors such as the presence of periapical lesions, severity of periodontal diseases, and the extent of alveolar bone loss; and factors related to the morphology of the maxillary sinus, such as the measurement section and the sinus septa [8][9][10]. Reports have indicated ostium obstruction in 59.3% of patients with SMT > 5 mm [11].…”
Section: Introductionmentioning
confidence: 99%
“…A high percentage of maxillary sinuses have bone septa within them, with variable sizes, localizations and thicknesses, making it an even more difficult task to detach the sinus floor membrane from the bone and create space to place the graft 5,6 . Studies have demonstrated that the presence of sinus septa was a predominant risk factor for perforation of the membrane in maxillary sinus lift processes using a lateral approach [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%